Improving Library Management by Using Cost Analysis Tools: A Case Study for Cataloguing Processes - Siguenza-Guzman, Lorena; Van den Abbeele, Alexandra; Cattrysse, Dirk (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2014)
TTDABC is a relatively new costing management technique, initially developed for manufacturing processes, which is gaining attention in libraries. This is because TDABC is a fast and simple method that only requires two parameters, an estimation of time required to perform an activity and the unit cost per time of supplying capacity. A few case studies have been documented with regard to TDABC in libraries; all of them being oriented to analyse specific library activities such as inter-library loan, acquisition and circulation processes. The primary focus of this paper is to describe TDABC implementation in one of the most important library processes, namely cataloguing. In particular, original and copy cataloguing are analysed through a case study to demonstrate the applicability and usefulness of TDABC to perform cost analysis of cataloguing processes.